2007
DOI: 10.1007/s11373-007-9212-0
|View full text |Cite
|
Sign up to set email alerts
|

Cholestin (Monascus purpureus rice) inhibits homocysteine-induced reactive oxygen species generation, nuclear factor-κB activation, and vascular cell adhesion molecule-1 expression in human aortic endothelial cells

Abstract: Hyperhomocysteinemia is associated with dysfunction and an independent risk factor of cardiovascular diseases. Cholestin (Monascus purpureus-fermented rice), contains a naturally-occurring statin, which has lipid-modulating and anti-inflammatory effects. We investigated the effects of Cholestin extract on the expression of vascular cell adhesion molecule-1 (VCAM-1) by homocysteine (HCY)-treated human aortic endothelial cells (HAECs). Supplement of HAECs with Cholestin extract significantly suppressed cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 57 publications
1
29
0
1
Order By: Relevance
“…Epidemiological studies indicate that RYR consumption is associated with reduced coronary heart disease risk [29, 30]. In vitro investigations have indicated that RYR can inhibit several key events of the atherogenic process, such as vascular smooth muscle and endothelial cell dysfunction by redox-sensitive mechanisms [15, 16, 31]. RYR contains chemicals that are similar to prescription statin medications including monacolin K (the same structure as the drug lovastatin).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Epidemiological studies indicate that RYR consumption is associated with reduced coronary heart disease risk [29, 30]. In vitro investigations have indicated that RYR can inhibit several key events of the atherogenic process, such as vascular smooth muscle and endothelial cell dysfunction by redox-sensitive mechanisms [15, 16, 31]. RYR contains chemicals that are similar to prescription statin medications including monacolin K (the same structure as the drug lovastatin).…”
Section: Discussionmentioning
confidence: 99%
“…RYR (LipoCol Forte) was obtained from NatureWise Biotech & Medicals Corporation (Taipei, Taiwan) and extracted at room temperature [15, 16]. Final concentration of solvents in following studies was always less than 0.5% to avoid potential interference.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current studies showed Hongqu contained many kind of useful compounds, such as monacolins (a group of antihyper-cholesterolemic agent), GABA (a kind of hypotensive agent) and a group of edible pigments (widely used as a natural food colorant) (Lin et al 2008a). Recent studies demonstrated that Cholestin (Monascus purpureus rice) may be a potential implication to attenuate homocysteine-stimulated activation of the endothelium (Lin et al 2008b) and M. purpureus rice may be an effective and economic treatment strategy for nephrotic dyslipidemia (Gheith et al 2008). Therefore, more research was needed regarding the utility of Monascus species.…”
Section: Introductionmentioning
confidence: 89%
“…Hyperhomocysteinemia is associated with dysfunction and risk factor of cardiovascular diseases. Lin et al (2008) investigated the effect of cholestin extract on the expression of vascular cell-adhesion molecule-1 (VCAM-1) by homocysteine (HCY) treated human aortic endothelial cells. The experiment showed that RYR extract significantly suppresses the cellular binding of human monocytic cells to HCY stimulated endothelial adhesion.…”
Section: Role Of Ryr In Cvdmentioning
confidence: 99%